Kontribusi Latihan Fartlek Terhadap Peningkatan Vo2max Atlet Porprov Bola Tangan Kabupaten Gresik Tahun 2023 - Ragil Joyo; Sulistyarto, Soni; Fithroni, Hijrin; Dzul Fikri, Muhammad (Jayabama: Jurnal Peminat Olahraga, 2024)
This research aims to fill the information gap and provide a comprehensive understanding of the contribution. of fartlek training to the improvement of VO2Max in Handball athletes from Gresik Regency's Porprov team.Handball is a sport that requires optimal physical fitness, including a high level of capacity at maximum oxygen (VO2Max). VO2Max is an important measure in evaluating aerobic fitness and athlete performance. Fartlek training, which involves varying intensity and speed in structured training sessions, is sufficient to provide satisfactory results in increasing maximal oxygen capacity or VO2Max in various types of sports. However, this study on how fartlek training contributes to increased VO2Max in handball athletes is still limited. The study will provide practical recommendations of exercises and their performance in preparation for the Porprov competition. This study was carried out with the intention of gaining an understanding of the presence or absence of the contribution of fartlek training to the increase in VO2Max of Gresik Handball athletes. By using the quasi experiment method with a one group pretest-posttest design in this study. The population in the study was 20 Gresik Regency Handball athletes. Sampling technique with purposive sampling. The study sample consisted of 14 Gresik Regency Handball athletes with 18 meetings including meetings for pretest and posttest. His research instrument is Mulstistage Fitness Test. Using t-test data analysis techniques, significance values to compare differences between before and after fartlek exercise treatment in increasing VO2Max. The results of the paired sample t-test analysis showed a p-value (sig) of 0.000. With a significance value of 0.000 that is smaller than 0.05, it can be concluded that there is a significant impact. Therefore, it can be concluded that fartlek training contributes significantly to the increase in VO2Max of Gresik Regency Porprov Handball athletes.